معدل الانتشار المصلي لعدوى Toxoplasma gondii وعوامل الخطورة المرتبطة بها بين النساء الحوامل المترددات على مستشفى تامزاوة التخصصي بجنوب ليبيا: دراسة مقطعية (Al-Farooq Journal of Sciences, 2026)
Toxoplasma gondii is a globally widespread protozoan parasite, and primary infection during pregnancy poses a significant risk to the fetus, potentially leading to miscarriage or congenital abnormalities. This study aimed to determine the seroprevalence of T. gondii infection among pregnant women attending Tamzawa Specialized Hospital in southern Libya and to identify factors associated with an increased risk of infection. A cross-sectional study was conducted between August 1 and September 10, 2025, involving 90 pregnant women. Venous blood samples were collected and tested for anti-T. gondii IgG and IgM antibodies using Chemiluminescence Immunoassay (CLIA) on the MAGLUMI analyzer. Demographic and clinical data were obtained using a structured questionnaire and analyzed with SPSS software. The overall seroprevalence of T. gondii antibodies was 18.89% (17/90). Chronic infection (IgG) accounted for 14.44%, mixed infection (combined IgG and IgM positivity) for 3.33%, and acute infection (IgM) for 1.11%. The prevalence increased with age, reaching 30.43% among women aged 36–45 years compared with 5.0% in the youngest age group; however, the difference was not statistically significant (P > 0.05). No significant association was found between T. gondii infection and the investigated risk factors, although higher seroprevalence was observed among women who kept cats (40%) and those with frequent soil contact (26.32%). The observed seroprevalence indicates continued exposure of pregnant women in southern Libya to T. gondii infection, highlighting the importance of routine early serological screening during pregnancy and strengthening health education and awareness programs.